Thermal and functional properties of starch extracted from tubers cultivated in the Ecuadorian Andean region - Lady Mireya QUEZADA-CORREA; Oscar CONTRERAS-DIOSES; Edison Omar MARTÍNEZ-MORA; Carlos Alberto GÓMEZ-ALDAPA; Esther RAMÍREZ-MORENO; Fabian Patricio CUENCA-MAYORGA (Acta Agriculturae Slovenica)
Thermal and functional properties of starch extracted from American taro and Indian shot were determined to assess their use in food products. Starch was extracted by the wet-milling method. Physicochemical composition was determined following the Association of Official Agricultural Chemists (AOAC) protocols. Total fibre was measured by the Total Dietary Fiber Assay Kit. The morphology of starch granules was observed by scanning electronic microscopy (SEM). Gelatinization temperature and viscosity were measured by Differential Scanning Calorimetry (DSC) and with a rapid viscosity analyser (RVA), respectively. Swelling capacity, solubility index, and absorption index were measured at 15, 60, 70, 80, and 90 °C. The yield for Indian shot (72.5 %) was higher of that for taro (60.2 %). No significant differences (p > 0.05) were found for moisture, ashes, total fibres, and protein; significant differences were found for fat content, total carbohydrates, amylose, and amylopectin. Granules of Indian shot starch featured ovoid shapes (diameter, 30 µm), while granules of American taro starch presented round shapes (diameter, 15 µm. Gelatinization temperature for American taro (78.33 °C) was higher of that for Indian shot (65.28 °C). Maximum viscosity in Indian shot (3,535.5 cP) was higher of that in American taro (2,446.5 cP). Concerning functional properties, Indian shot starch yielded higher values. Moreover, at high temperature values, American taro starch presented better gelling results than those in Indian shot.